On Characterizing the Interactions between Proteins and Guanine Quadruplex Structures of Nucleic Acids - McRae, Ewan K. S.; Booy, Evan P.; Padilla-Meier, Gay Pauline; McKenna, Sean A. (Journal of Nucleic Acids, 2017)
Guanine quadruplexes (G4s) are four-stranded secondary structures of nucleic acids which are stabilized by noncanonical hydrogen bonding systems between the nitrogenous bases as well as extensive base stacking, or pi-pi, interactions. Formation of these structures in either genomic DNA or cellular RNA has the potential to affect cell biology in many facets including telomere maintenance, transcription, alternate splicing, and translation. Consequently, G4s have become therapeutic targets and several small molecule compounds have been developed which can bind such structures, yet little is known about how G4s interact with their native protein binding partners. This review focuses on the recognition of G4s by proteins and small peptides, comparing the modes of recognition that have thus far been observed. Emphasis will be placed on the information that has been gained through high-resolution crystallographic and NMR structures of G4/peptide complexes as well as biochemical investigations of binding specificity. By understanding the molecular features that lead to specificity of G4 binding by native proteins, we will be better equipped to target protein/G4 interactions for therapeutic purposes.